2011
DOI: 10.1007/s10549-011-1716-7
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and breast cancer survival: an epigenetic link through reduced methylation of a tumor suppressor gene L3MBTL1

Abstract: The study was conducted to determine the effect of physical activity on DNA methylation and to predict the consequence of this effect concerning gene expression and breast cancer survival. Blood samples, collected from 12 breast cancer patients who participated in a randomized clinical trial of exercise, were examined for exercise-related changes in DNA methylation using a methylation microarray. Tumor samples of 348 breast cancer patients were analyzed with qRT-PCR and qMSP to determine gene expression and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 32 publications
0
65
0
1
Order By: Relevance
“…23,24 L3MBTL1, on the other hand, is a tumor suppressor gene that appears to suppress genes and microRNAs that re-activate during tumor growth and whose expression is associated with decreased risk of death due to breast cancer. 25 We found suggestive evidence of association for anti-CMV antibody level on chromosome 14, with our top SNP located nearest to the pseudogene LOC728667. However, the nearby DHRS4 gene may be of interest in this trait as it is involved in retinol metabolism.…”
Section: Discussionmentioning
confidence: 55%
“…23,24 L3MBTL1, on the other hand, is a tumor suppressor gene that appears to suppress genes and microRNAs that re-activate during tumor growth and whose expression is associated with decreased risk of death due to breast cancer. 25 We found suggestive evidence of association for anti-CMV antibody level on chromosome 14, with our top SNP located nearest to the pseudogene LOC728667. However, the nearby DHRS4 gene may be of interest in this trait as it is involved in retinol metabolism.…”
Section: Discussionmentioning
confidence: 55%
“…Nakajima et al [57] described lower, age-dependent reductions of ASC gene methylation, which encodes for proinflammatory cytokines, in exercising individuals. Further, Zeng et al [91] were able to show that exercise leads to the hypomethylation of a breast cancerspecific tumor supressor gene.…”
Section: Counterbalance Of Tumor-induced Cachexia Through Physical Exmentioning
confidence: 99%
“…It has also been reported that the myogenic genes in human skeletal muscle are altered by physical activity [125]. In addition, it has been found that epigenetic regulation of the tumor suppressor gene, L3MBTL1, has a favorable impact on survival outcomes of breast cancer patients [126]. However, how physical exercise affects oncogenes through alternating epigenetic regulation remains a question.…”
Section: Epigenetic Regulationmentioning
confidence: 99%